2009
DOI: 10.4021/gr2009.06.1299
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers in the Pathogenesis of Cholangiocarcinoma: Potential for Early Detection and Selection of Appropriate Treatment

Abstract: Cholangiocarcinoma (CC) is a primary malignancy that arises from cholangiocytes, the epithelial cells lining the bile duct livers. The worldwide incidence of CC is increasing and despite of combined therapeutic strategies, its prognosis remains poor. Till now surgery remains the only curative treatment modality. Over the past years, several important studies have yielded new insights into the molecular mechanisms of cholangiocarcinoma. This review focused on critical molecular player during the development fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Another suggested mechanism is the inflammatory molecules. Multiple inflammatory cytokines were found to be elevated in obesity including interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) and both were found to promote cholangiocarcinoma growth [11,[35][36][37].…”
Section: Obesity and Cholangiocarcinomamentioning
confidence: 99%
“…Another suggested mechanism is the inflammatory molecules. Multiple inflammatory cytokines were found to be elevated in obesity including interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) and both were found to promote cholangiocarcinoma growth [11,[35][36][37].…”
Section: Obesity and Cholangiocarcinomamentioning
confidence: 99%
“…In 2016, it is estimated that more than 35,000 people in the U.S alone will be diagnosed with HCC. This number has been steadily increasing by about 3–4% annually over the last 10 years; overall, the incidence has tripled since the 1980s [ 55 , 56 ]. Viral hepatitis was once the leading cause of HCC worldwide.…”
Section: Hepatocellular Cancermentioning
confidence: 99%
“…Studies have demonstrated that serum leptin levels are increased in obesity and have been suggested as a risk factor for CC [ 66 ]. Besides leptin, other pro-inflammatory cytokines - Interleukin-6 (IL-6) and tumor necrosis factor (TNF) are linked strongly to obesity and have been found to have a role in development of CC [ 56 ]. Based on the current literature review, evidence of association of obesity with CC is growing and needs to be confirmed with long-term cohort studies.…”
Section: Cholangiocarcinomamentioning
confidence: 99%